Bir mühtedî sadrazam: İzmirli Salih Paşa (-- -1828) - Doğan, Kemal (My University, 2015)
Osmanlı padişahı II. Mahmud’un sadrazamı olarak 18 ay görev yapmış olmasına rağmen mühtedî Salih Paşa, muhtemelen, döneminin sevilmeyen fakat güçlü şahsiyeti Halet Efendi’nin gölgesinde kaldığı için Osmanlı tarihçileri arasında dahi pek bilinmemektedir. Hakkında yayınlanmış tek bir makale bile bulunmamasını başka türlü izah etmek mümkün görünmemektedir. Osmanlı vakanüvislerinin kaydettiği bilgi onun İzmir doğumlu olduğu ve İstanbul’a gelerek ihtida ettiği, arpa emini olarak devlet görevine başladığını, Rum ayaklanması sırasında sadrazamlık yaptığı, ardından iki kez Şam valiliğinde bulunduğuyla sınırlıdır. Bu araştırma, Salih Paşa’nın siyasi hayatını neredeyse bütünüyle Osmanlı arşivi belgelerine dayanarak gün ışığına çıkarmayı amaç edinmiştir. Salih Paşa, II. Mahmud, Halet Efendi, arpa emini, baruthaneler nazırı, sadaret kaymakamı, Şam valisi, mühtedî, Hac emiri.

Salih Pasha the convert is not known much even among the Ottoman historians although he served as the grand vizier of Ottoman Monarch Mahmud II for eighteen months, because he was in the shadow of Halet Efendi, the powerful but disliked statesman of the period. Otherwise, there seems to be no way of explaining the fact that there is no single article about him. Ottoman chroniclers of the period state that he was born in İzmir, he converted to Islam in İstanbul when he was young, and he began serving as the master of the barley, who is responsible for feeding of the royal horses, he became the grand vizier during the Greek uprising, and then served as the governor of Damascus twice. This study aims to reveal his political life almost exclusively based on the documents from Ottoman archives. Salih Pasha, Mahmud II, Halet Efendi, master of barley, minister of powdermills, deputy grand vizier, governor of Damascus, convert, master of Pilgrimage.
Keywords: Osmanlı İmparatorluğu, 1299-1918; Tarih; Türkiye